Ionic liquids in dispersive liquid-liquid microextraction - Trujillo-Rodríguez, María J.; Rocío-Bautista, Priscilla; Pino, Verónica; Afonso, Ana M. (TrAC, Trends in analytical chemistry (Regular ed.), 2013)
•Ionic liquids (ILs) applied in dispersive liquid-liquid microextraction (DLLME).•Dispersive solvents (organics, surfactants or hydrophilic ILs) not always needed.•Summary of determinations of metals and organic compounds in various samples.•IL-based surfactants can be used for solids analysis and in-situ IL-DLLME. In this review, we summarize the most recent analytical developments aimed at employing Ionic liquids (ILs) in dispersive liquid-liquid microextraction (DLLME). Four main operation modes can be distinguished: (1) conventional IL-DLLME; (2) temperature-controlled IL-DLLME; (3a) ultrasound-assisted, (3b) microwave-assisted or (3c) vortex-assisted IL-DLLME; and, (4) in-situ IL-DLLME. In these modes, the dispersive solvent can be an organic solvent, a surfactant, or a hydrophilic IL. In some cases, a dispersive solvent is not even necessary. We discuss practical applications of IL-DLLME to determine metals and organic compounds in a variety of samples.